Does liquidity drive stock market returns? the role of investor risk aversion - Zhang, Qingjing; Choudhry, Taufiq; Kuo, Jing-Ming; Liu, Xiaoquan (2021)
In this paper, we explore the relations between liquidity, stock returns, and investor risk aversion as captured by the variance risk premium (VRP). This is motivated by theoretical and empirical evidence in the literature which suggests that investor risk aversion negatively correlates with asset liquidity, and ample empirical evidence documenting liquidity risk premium. We use monthly US data from January 1999 to December 2018 and show that innovations in the VRP Granger-cause stock returns, which in turn drive liquidity. Our findings are consistent with predictions of prior theories and highlight the predictability of the VRP. They also contribute to the on-going debate on the causal relation between stock returns and liquidity. Finally, we explore the channels through which the VRP impacts liquidity and find that the VRP influences market and momentum factors, and that movements in these factors lead to changes in liquidity. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.